In vivo and In vitro anti-diabetic effects of cinnamon (Cinnamomum sp.) plant extract: A review - Alyssa MA Nazareno; Listya Purnamasari; Joseph F dela Cruz (jurnal1, 2022)
Research regarding the enormous potential of medicinal plants for the development of new drugs and the efficient treatment of diabetes mellitus is increasing due to the harmful effects that synthetic drugs may bring such as severe hypoglycemia, abdominal discomfort, lactic acidosis, and more. Cinnamomum sp. (cinnamon) extracts have shown to have significant anti-diabetic effects on type 2 diabetes mellitus in experimental rodent animals in a dose-dependent manner. There are different possible mechanisms of action involved in its anti-diabetic activities. The efficacy of cinnamon extract as an anti-diabetic agent in type 1 diabetes mellitus experimental rodent animal studies explored in this study.